Effect of the itinerant electron density on the magnetization and Curie temperature of Sr2FeMoO6 ceramics - Wang, Jin-Feng; Shi, Teng-Fei; Zhuang, Zhao-Tong; Gao, Qian-Qian; Zhang, Yan-Ming (RSC advances, 2018)
The itinerant electron density (n) near the Fermi level has a close correlation with the physical properties of Sr2FeMoO6. Two series of single-phase Sr(2−y)NayFeMoO6 (y = 0.1, 0.2, 0.3) and Sr(2−y)NayFe(1−x)Mo(1+x)O6 (y = 2x; y = 0.1, 0.2, 0.3) ceramics were specially designed and the itinerant electron density (n) of them can be artificially controlled to be: n = 1 − y and n = 1 − y + 3x = 1 + 0.5y, respectively. The corresponding crystal structure, magnetization and the ferromagnetic Curie temperature (TC) of two subjects were investigated systematically. The X-ray diffraction analysis indicates that Sr(2−y)NayFeMoO6 (y = 0.1, 0.2, 0.3) have comparable Fe/Mo anti-site defect (ASD) content in spite of decreased n. However, a drastically improved Fe/Mo ASD can be observed in Sr(2−y)NayFe(1−x)Mo(1+x)O6 (y = 2x; y = 0.1, 0.2, 0.3) caused by the intrinsic wrong occupation of normal Fe sites with excess Mo. Magnetization–magnetic field (M–H) behavior confirms that it is the Fe/Mo ASD not n that dominantly determines the magnetization properties. Interestingly, approximately when n ≤ 0.9, TC of Sr(2−y)NayFeMoO6 (y = 0.1, 0.2, 0.3) exhibits an overall increase with decreasing n, which is contrary to the TC response in electron-doped SFMO. Such abnormal TC is supposed to relate with the ratio variation of n(Mo)/n(Fe). Moreover, when n ≥ 1, TC of Sr(2−y)NayFe(1−x)Mo(1+x)O6 (y = 2x; y = 0.3) exhibits a considerable rise of about 75 K over that of Sr(2−y)NayFe(1−x)Mo(1+x)O6 (y = 2x; y = 0.1), resulting from improved n caused by introducing excess Mo into Sr(2−y)NayFeMoO6. Maybe, our work can provide an effective strategy to artificially control n and ferromagnetic TC accordingly, and provoke further investigation on the FeMo-baseddouble perovskites.